Biomechanical evaluation of head and neck injuries during head-first falls in skiing - Zhang, K.; Wang, D. (Computer Methods in Biomechanics and Biomedical Engineering, 2026)
Skiing accidents may lead to severe head and neck injuries. This study uses the THUMS model to evaluate the initial conditions and related injury mechanisms of head impacts with the snow surface during skiing falls. Initial speed was found to be the main factor affecting head injury criterion (HIC). Impact position is the key factor affecting cervical curvature. Rear impacts cause excessive cervical spine extension, while frontal impacts cause excessive cervical spine flexion. Rear impacts are more likely to cause neck injuries. As the angle and speed increase, the degree of cervical spine injury also increases.